Sleep duration, daytime napping and the risk of incident metabolic syndrome vary by age and sex: findings from the China health and retirement longitudinal study - Bowen Zhang; Weijia Liu; Jingrui Wang; Lulu Zhang; Ke Wang; Peixi Wang (BMC Public Health)
Abstract Objective Currently, the association of sleep duration and daytime napping with the prevalence of metabolic syndrome (MetS) is still controversial. This study was designed to explore the association between sleep duration, daytime napping and MetS by age and sex in Chinese adults. Methods Data were obtained from the 2011 and 2015 waves of the China Health and Retirement Longitudinal Study (CHARLS). Participants with MetS at baseline or with missing data were excluded, leaving 2803 participants (≥ 45 years old) who completed follow-up and were included in the longitudinal analysis. Sleep duration and daytime napping were determined by self-reported questionnaires. Medical conditions, including MetS, dyslipidaemia, hypertension, and diabetes mellitus, were determined from a fasting blood specimen and physical exam at the baseline visit. Logistic regression models were performed to explore the longitudinal associations of baseline napping and sleep duration with MetS and its occurrence. Results During a median follow-up period of 4 years, 616 participants (22.0%) developed new-onset MetS. Compared with non-napping, longer daytime napping (> 30 min/day) was significantly associated with the occurrence of MetS (OR: 1.247, 95% CI: 1.001, 1.554), and a significant association was still present after adjustment for each of the covariates. In the subgroup analysis, longer daytime napping (> 30 min/day) was also significantly associated with MetS in elderly females (OR: 1.946, 95% CI: 1.226, 3.090). Moreover, sleep duration was not significantly associated with MetS in our study. Conclusion A longer napping duration is associated with an increased risk of MetS in an older Chinese population, and this association differed according to sex.